FINDING WAYS TO GROWING SMEs in WEST JAVA - Iqbal Arraniri; Oding Syafrudin; Heni Susilawati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
The number of micro, small and medium enterprises (SMEs) in 2019, recorded 42 million business units. Thus the majority of our economic actors are small and medium enterprises. In addition, this sector also absorbs 79 million people from the 100 million Indonesian workforce. Therefore, it is necessary to make various efforts to develop small businesses in Indonesia, so that this sector develops better. SMEs that are able to survive for a long time are industries that are able to anticipate changes in every era. Those who are able to withstand the conditions of the times are those who are able to adapt to changes and are able to build networks. Every UKM has a goal to achieve growth and survival for the long term. In the current era of globalization, where competition between companies is getting tighter. SMEs are required to have the ability to develop strategic choices in the field of marketing management so that they are able to adapt to the adaptability of a dynamic business environment. Seeing this fact, the company must be managed with systematic and dynamic efforts to benefit from the ever-changing market developments. For this study, the population used was 157 batik business owners in Cirebon Regency. The sampling technique used in this study was a non-probability technique, non-probability sampling by means of a census. With this method, researchers used the entire population as the sample because the population was relatively small for the size in the SEM model. Keywords : Entrepreneurial Orientation, Adaptability of The Business Environment, Quality of Business Strategy, Competitive Advantage, SMEs Performance, SEM